Routledege handbook of Japanese culture and society - Lyon-Bestor, Victoria; Bestor, Theodore C.; Yamagata, Akiko (Routledge, 2011)
The Routledge Handbook of Japanese Culture and Society is an interdisciplinary resource that focuses on contemporary Japan and the social and cultural trends that are important at the beginning of the twenty-first century. This Handbook provides a cutting-edge and comprehensive survey of significant phenomena, institutions, and directions in Japan today, on issues ranging from gender and family, the environment, race and ethnicity, and urban life, to popular culture and electronic media. Written by an international team of Japan experts, the chapters included in the volume form an accessible and fascinating insight into Japanese culture and society. As such, the Handbook will be an invaluable reference tool for anyone interested in all things Japanese. Students, teachers and professionals alike will benefit from the broad ranging discussions, useful links to online resources and suggested reading lists. The Handbook will be of interest across a wide range of disciplines including Japanese Studies, Cultural Studies, Anthropology, Sociology and Asian Studies in general.